Structural diversity in coordination polymers with benzenetetracarboxylate and bis-pyridyl-bis-amide - Liao, Tsung-Te; Usman, Muhammad; Ye, Yu-Hui; Bahadur Thapa, Kedar; Chen, Jhy-Der (Inorganica Chimica Acta, 2025)
[Display omitted] •Four coordination polymers constructed from flexible bis-pyridyl-bis-amide (boba) and tetracarboxylic acid are reported.•Rare structures are observed for these coordination polymers.•The metal effect on the structural diversity of the CPs supported by the 1,2,4,5-BETC4- is subject to the change of the flexibility of the bpba ligand. Reactions of N‚N’-bis(3-methylpyridyl)oxalamide (L1), N‚N’-bis(3-methylpyridyl)adipoamide (L2) or N‚N’-bis(3-methylpyridyl)sebaamide (L3) with 1,2,4,5-benzenetetracarboxylic acid (1,2,4,5-H4BETC) and metal salt yield four coordination polymers: {[Cu2(L1)2(1,2,4,5-BTEC)(H2O)]·5H2O}n, 1, [Cu2(L2)(1,2,4,5-BTEC)(H2O)4]n, 2, [Cu2(L3)(1,2,4,5-BTEC)(H2O)4]n, 3, and [Ni(L2)(1,2,4,5-BTEC)0.5(H2O)2]n, 4. These polymers have been structurally characterized using single crystal X-ray crystallography. Complex 1 forms a 3D framework adopting a new (4.62)2(42.62.82)(42.64.84)2(63.83) topology, whereas the others display 2D layers with the bex topology for 2 and 3, and a rare 4,4L88 topology for 4. The structural diversity of these coordination polymers is influenced by the combined effects of metal identity and ligand flexibility, supported by the 1,2,4,5-BTEC4- ligand. Their thermal properties have also been investigated.